Pengaruh Pendapatan, Total Hutang, dan Ukuran Perusahaan terhadap Laba Bersih pada Perusahaan yang Terdaftar di Jakarta Islamic Index (JII) Periode 2021-2024 - Siti Kayla Maghfirah; Khadijah Nurani (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2026)
This study aims to determine the effect of revenue, total debt, and company size on net profit of companies listed on the Jakarta Islamic Index (JII) for the 2021–2024 period. The research data is secondary data in the form of financial reports published on the official website of the Indonesia Stock Exchange. The sampling technique used was purposive sampling, resulting in 15 companies across a four-year period. This study employed a quantitative approach with panel data regression analysis.              The t-test results indicate that revenue has a positive and significant effect on net profit, with a t-value (6.693448) > t-table (2.00324) and a probability value (0.0000) < (0.05). Total debt does not significantly affect net profit, with a t-value (0.255620) < t-table (2.00324) and a probability value (0.7992) > significance value (0.05). Company size does not have a significant effect on net profit with a calculated t value (0.782000) < t table (2.00324) and a probability value (0.4375) > significance value (0.05). The results of the f test show that the three X variables simultaneously affect net profit with calculated F > F table, namely 20.27371 > 2.77 and a probability value < significance value, namely 0.000000 < 0.05.